Bioactivity of the organic extracts of Cnidoscolus urens (L.) Arthur (Euphorbiaceae) on the cabbage-caterpillar - Carvalho Neto, Moisés Felix de; Gonçalves Gervásio, Rita de Cássia Rodrigues; Araújo, Edigênia Cavalcante da Cruz; Almeida, Jadson Cardoso de; Oliveira, Ana Paula de (Comunicata Scientiae, 2018)
The aim of the current study was to identify the phytochemical profile of several different fractions of the ethanolic extract taken from the cansanção-nettle leaves, as well as assess the bioactivity on Ascia monuste orseis. After gathering the plant samples, the species was identified, and the organic extracts were collected after processing was completed in the laboratory. The fractions obtained were as follows: hexane (Hex-F), chloroform (CHCl3-F), ethyl acetate (AcOEt-F) and methanolic (MeOH-F). In the context of the insect, the biological parameters evaluated included the incubation period, egg viability, length of the larval stage and mortality, pupal viability and weight, number of defective adults and leaf consumption. The extracts revealed a large percentage of anthraquinones, coumarins, anthracene derivatives, terpenes and steroids and water-soluble tannins. All the organic extracts were confirmed to exert a negative effect on the embryonic, larval, pupal and adult phases of the cabbage-caterpillar, implying that the chloroform fraction induced 100% mortality in this pierid. It was also possible to verify that all the fractions also affected the feeding behavior of the cabbage-caterpillar, decreasing the leaf consumption by the larvae during the organic extract treatments.